AN ECONOMIC ANALYSIS OF DETERMINANTS OF HOUSE RENTS IN THE UNIVERSITY ENVIRONMENT - Sikiru Jimoh Babalola; Abdulrazaq Isa Umar; Luqman Adedamola Sulaiman (European Scientific Journal, ESJ, 2013)
This study investigates the factors determining house rental rates in the university environment. The study applies a Hedonic pricing model, which captures multi-dimensional characteristics of the houses in the sample. The findings provide answers to the research questions after leaving out two variables from the model because of exact collinearity and orthogonality. Variables like age, life span of house, tenement rate charges by the local government, and number of houses built in the university environment are the key determinants of house rent. It is found that people do not obtain mortgage loans to build their houses. The study recommends that policies and strategies like regulatory measures, direct construction of houses, provision of finance, land reforms, rent control and anti-inflation taskforce should be adopted.